Evaluation of Asthma Course in Patients Hospitalized in Pediatric Intensive Care Unit Due to Severe Asthma Exacerbation - Ahmet Selmanoglu; Hatice Irmak Celik; Cankat Genis; Esra Kockuzu; Zeynep Sengul Emeksiz; Emine Dibek Misirlioglu (Medicina)
Background and Objectives: Childhood asthma represents a significant global public health issue and is the most common chronic disease among children. Hospitalization costs, especially for intensive care, are quite high. This study aimed to evaluate the characteristics, prognosis, and preventable risk factors of patients admitted to the Pediatric Intensive Care Unit (PICU) due to severe asthma exacerbations. Materials and Methods: We assessed patients admitted to the Ankara Bilkent City Hospital PICU from January 2013 to December 2022 diagnosed with asthma based on The Global Initiative for Asthma (GINA) criteria. The collected data encompassed demographic and clinical characteristics, intensive care treatments, hospitalization duration, atopic conditions, and respiratory viral panel results. The current clinical status was assessed using hospital records and caregiver interviews, with a focus on recent emergency admissions, ongoing treatments, exacerbation frequency, and asthma control based on GINA guidelines. Results: The study comprised 83 patients with a mean age of 72.9 (±45.5) months, predominantly male (63.9%). The average follow-up duration post-discharge was 40.7 ± 26.9 months. Patients received respiratory support in the PICU for a mean of 3.8 (±2.8) days and systemic steroid therapy for 4 (±1.5) days. Respiratory viral panel results identified pathogens in 42 patients, with rhinovirus being the most frequent. Post-discharge, 72.3% of patients continued follow-up at pediatric allergy clinics. Of the 60 patients contacted, 67.5% were on current asthma treatment and 48.2% had experienced an exacerbation in the past year. Asthma management steps remained unchanged for 33 patients, decreased for 13, and increased for 47 (44.6%). Asthma maintenance treatments pre-admission and post-discharge showed that 44.6% (n = 47) of the patients required an increase in their GINA treatment step after PICU admission, which was statistically significant (p < 0.001). History of atopic dermatitis was a significant risk factor for escalating treatment steps in both univariate and multivariate analyses (p = 0.018, p = 0.03). Conclusions: We found that admission to the PICU due to severe asthma exacerbation not only increases the risk of recurrent asthma exacerbations but also serves as a risk factor for stepping up maintenance treatment according to GINA guidelines during long-term follow-up.